Visual scale of MRI evaluation of the brain atrophy on early stage of Alzheimer disease - N. G. Neznanov; N. I. Ananyeva; N. M. Zalutskaya; I. R. Stulov; I. E. Galsman; J. A. Beltceva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
One of the most important parts in biomarkers research is finding of atrophic changes in strategic for cognition brain structures. In the study one of the structural neurovisual bi-omarkers of neuronal damage were analised - MRI visual scale of atrophy. 94 patients with early signs of Alzheimer disease were examined. Using of visual scales show atrophy slight and mild of mediobasal temporal lobe in 64 patients (68%), interuncal distance was Increased in 27 patients (28%). Atrophic changes of the cortex of parietal lobe were not found in most of patients.